Milkira Foods Ltd - Anuradha; Kumar, Prem (Gyan Management Journal, 2011)
Welcome" said victor to Professor Aru. Victor, the Managing Director of Milkira Foods Ltd had invited Professor Aru from the Regional Business School when they met at a social get together a few days ago. Victor found talking to the Professor interesting and useful for his business."Thank You" said the Professor ushering in and settling in the chair offered by Victor. After discussing about the business and common friends, both of them came to the business of Milkira. Victor started narrating the story as if going down the memory lane:"Milkira is a diversified food products manufacturing and food service of North India.It was established by my mother, a passionate food aficionado, three decades ago in 1977 from the family kitchen. Milkira offers today a range of sauces, mayonnaises, toppings, syrups, biscuits, Indian snack foods, stabilizer blends and ice creams. Through its commitment to taste and quality Milkira has emerged as a preferred consumer brand and a leading supplier to Indian and global food majors"